Study on the Coupling Coordination of Urban Infrastructure and Population in the Perspective of Urban Integration - Cheng Lu; Wenxia Hong; Yiting Wang; Defeng Zhao (IEEE Access, 2021)
The continuous development of urbanization and the integration of urban agglomerations are accompanied by the outbreak of the contradiction between urban infrastructure and population. Therefore, the study of the coupling coordination relationship between urban infrastructure and population is of great significance for the benign development of cities and the in-depth integration of urban agglomerations. In order to measure the coupling coordination between urban infrastructure and population accurately and objectively, we construct the evaluation index system of urban infrastructure supply level and population development level based on biblio-metrics method, determine index weights using G1 and standard variance method, then construct a coupled coordination model from four aspects: population, infrastructure, population and infrastructure, and relative lag. Next, a case study is conducted subsequently using the Qingdao, Yantai, and Weihai in China as examples. The results show that the coupling relationship between infrastructure and population will synergistically affect urban development, and has obvious temporal characteristics. Qingdao, Yantai and Weihai have initially built the prototype of metropolitan area, changing from population development lagging city to infrastructure lagging city. The research results are of great significance to the further research of urban agglomeration integration, can provide necessary reference data for the planning and construction of Jiaodong Economic Circle, help to quantify the relevant problems in the integration process of other urban areas.